13cRA regulates the differentiation of antler chondrocytes through targeting Runx3. (16th January 2017) - Zhang, Hong‐Liang; Cao, Hang; Yang, Zhan‐Qing; Geng, Shuang; Wang, Kai; Yu, Hai‐Fan; Guo, Bin; Yue, Zhan‐Peng
Abstract: Although 13cRA is involved in the regulation of cellular proliferation and differentiation, its physiological roles in chondrocyte proliferation and differentiation still remain unknown. Here, we showed that 13cRA could induce the proliferation of sika deer antler chondrocytes and expression of Ccnd3 and Cdk6. Administration of 13cRA to antler chondrocytes resulted in an obvious increase in the expression of chondrocyte marker Col II and hypertrophic chondrocyte marker Col X. Silencing of Crabp2 expression by specific siRNA could prevent the 13cRA‐induced up‐regulation of Col X, whereas overexpression of Crabp2 showed the opposite effects. Further study found that Crabp2 mediated the regulation of 13cRA on the expression of Runx3 which was highly expressed in the antler cartilage and inhibited the differentiation of antler chondrocytes. Moreover, attenuation of Runx3 expression greatly raised 13cRA‐induced chondrocyte differentiation. Simultaneously, 13cRA could stimulate the expression of Cyp26a1 and Cyp26b1 in the antler chondrocytes. Inhibition of Cyp26a1 and/or Cyp26b1 reinforced the effects of 13cRA on the expression of Col X and Runx3, while overexpression of Cyp26b1 rendered the antler chondrocytes hyposensitive to 13cRA. Collectively, 13cRA may play an important role in the differentiation of antler chondrocytes through targeting Runx3. Crabp2 enhances the effects of 13cRA on chondrocyte differentiation, while Cyp26a1 and Cyp26b1 weaken the sensitivity of antler chondrocytes to 13cRA.